Effect of Curing Method on Properties of Lightweight Foamed Concrete - Kado, Bishir; Mohammad, Shahrin; Huei Lee, Yeong; Ngian Shek, Poi; Aida Ab Kadir, Mariyana (International Journal of Engineering and Technology, 2018)
Lightweight construction is aimed to achieve a sustainable feature by reducing transportation frequency and construction materials usage during construction phase. Lightweight precast concrete may serve an alternative for the lightweight construction. There are rarely application can be found for structural members as lightweight panels always to be used for secondary or non-load bearing members. This paper presents an experimental study on properties (compressive strength, splitting tensile strength, water absorption) of lightweight foamed concrete (LFC) at two different curing methods. LFC with densities of 1500, 1700, and 1800 kg/m3, cement-sand ratio of 2:1 and water-cement ratio of 0.5 were investigated. The results showed LFC can be produced with the properties ofdensity range of 1500 to 1800 kg/m3 and corresponding compressive strength of 10 to 39 MPa. The higher the density of LFC, the less the water absorption for all the curing method considered, the highest and the lowest water absorption was 11.3% and 2.0% for 1500 kg/m3 cured in water and 1800 kg/m3 cured in air respectively. Compressive strength of LFC increases with age and density while water cured LFC has high compressive strength. Splitting tensile strength increases with density of LFC, but air cured LFC has more splitting tensile strength than water cured of the same density. The highest splitting tensile strength recorded was 3.92 MPa for 1800 kg/m3 cured in air, which was about 16% of its compressive strength at 28 days of curing age. These properties are important and can be applied to LFC precast structural members with air or water curing method which have less references for LFC in structural usage.Â Â